Knowledge, Attitude and Practice on Acute Respiratory Infections among Mothers in Two Rural Areas in Subang Subdistrict, West Java, Indonesia - Cissy B. Kartasasmita; Mintardaningsih Mintardaningsih; Anna Alisjahbana; Oma Rosmayudi; S. Hadyana (Paediatrica Indonesiana, 1999)
A survey was conducted in 2 rural villages in Indonesia. This study was a part of a one-year intervention study on case management of acute respiratory infections (ARI) in infants of less than 12 months old in Cisalak (VI, intervention village) and Sagalaherang (V2, control village). The aim of the study is to know the knowledge, attitude and practice (KAP) on ARI among rural villages mothers. All pregnant women and mothers with child below five years resided in those villages were included in the study. Trained field interviewers visited and interviewed mothers on several questions related to ARI using pretested questionnaire. A total of 436 and 576 mothers, with a mean age of25.4 (SD=5.7) and 26.5 (SD=5.4) years from VI and V2 respectively, were included. Most mothers had traditional beliefs that the cause of ARI was bad wind (77.3% and 73.8%, respectively), only 1.8% and 9.2% mothers know that ARI is caused by microorganisms. However, they believe that the disease is infectious (59.9% and 79.7%). Therefore, most mothers were aware and gave medication (66.5% and 36.3%) or brought the child to village health center (23.6% and 57.1%). The problems for seeking a medical help are transportation, distance and ignorance. As conclusion, we found that the present knowledge on ARI was in adequate, thus more information are needed for mothers to solve the ARI problems in rural villages.